Far Northern Section zoning plan : basis for zoning decisions - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 2002)
This document sets out the basis for the development of the zoning plan for the Far Northern Section of the Great Barrier Reef marine Park that was approved by the Federal Parliament in 2000.
Keywords: Marine parks and reserves; Zoning; Marine parks; Conservation; Coastal zone management; Planning; Environmental management; Legislative tools; Zones, plans and maps; Managing Multiple Use; Far Northern Management Area